The New Elite Prefers Quality - Lidin, Konstantin (project baikal, 2016)
Over the last fifty years, the quality of construction has been constantly declining in light of the ideology of fast updating of the whole sphere of consumption. As a result, the houses built in the 1950s remain elite, despite their respectable age. Bulgakov House (the object of the issue) is built in the historical center of Moscow. The high quality of its design and construction and careful and attentive treatment of the historic environment make this house an example of true elitism.